Electric powered irrigation systems : a case study in Bangladesh - Paul, Subhash Chandra; Gupta, C.P.; Murty, V.V.N.; Salokhe, Vilas M.; Wickramanayake, B.W.E.; Swidish International Development Cooperation Authority Environmental Program (SIDA-EP) (Bangkok : Asian Institute of Technology, 1995)
A case study was conducted in Tangail district of Bangladesh to study the present status and economics of electrified tubewell irrigation. In the study area investors provide irrigation water to a group of farmers' land based on s hare crop system. Th e cost analysis was carried out to estimate investors as well as farmers profit. Economics of irrigation in present versus potential command area and individual farmer versus investor was studied. To utilize t h e idle capacity of electric motor during off- irrigation season, economics of threshing paddy, rice mill and flour mill were studied. Selected integrated operations (irrigation to Boro and Aman rice, threshing and rice milling) for each irrigation unit was studied. Finally financial analysis of each project was carried out to make suitable recommendation to determine financial viability of project from investor's point of view. The study results indicated that growth of Low Lift Pumps (LLP) are decreasing, Deep Tubewells (DTW) are about to be stagnated and Shallow Tubewells (STW) are increasing rapidly with rapid expansion of electrified irrigation by Rural Electrification Board (REB). All irrigation schemes are profitable (except in sandy loam soil of present command area). Break-even command a rea of clay loam, silty loam, loam and sandy loam soil are 3.4 ha, 1.8 ha, 3.7 ha, and 9.0 ha, respectively. Break-even operating time of rice mill is 65 h, flour mill is 80 h and break-even point for mechanical thresher is 3.5 tons of paddy. cox, sox and NOx emitted by diesel engine pollute the environment by 1.71, 10 and 5.73 times, respectively as compared to an electric motor. In the stud y area motor power use efficiency is 343 to 563, conveyance efficiency is 403 to 493, pumping plant efficiency is 533 to 753, potential command area is 2.5 to 3.4 times of present command area, over irrigation is 193 to 843 based on soil and cropping intensity is 300%. Integrated operations based on soil can give 2.5 to 5.5 times of profit by covering present command area and it can be increased to 9-16 times by covering potential command area. Electricity supply by REB in single irrigation and in integrated projects at the marginal rate is suggested for sustainable development of agriculture in Bangladesh.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1995
Keywords: Irrigation farming -- Bangladesh